Cationically polymerizable curable composition
A cationic polymerization composition with specific acid and basic fillers and a photoacid generator addresses gelation and stability issues, ensuring effective curing and X-ray contrast in dental applications.
Patent Information
- Application Number
- JP2021001535
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-07
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-01-07
AI Technical Summary
Cationic polymerization compositions used in dental applications face issues with gelation during storage due to the presence of phenol-based oxidizers and hydrogen ion traps, which can inhibit curing speed and stability, especially when used in the oral cavity, and the use of X-ray optical fillers complicates X-ray contrast without compromising curing properties.
A cationic polymerization composition containing specific ratios of acid and basic fillers, with defined electrical negative levels and surface properties, combined with a cationic polymerization monomer and a photoacid generator, to prevent gelation and maintain curing stability over time, while allowing X-ray contrast.
The composition ensures long-term storage stability without gelation, maintains initial curing properties, and allows for X-ray contrast without the need for additional X-ray fillers, enhancing dental applications like fillings and adhesives.
Smart Images

Figure 0007622939000001 
Figure 0007622939000002 
Figure 0007622939000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a cationically polymerizable hardenable composition, particularly to a cationically polymerizable hardenable composition that can be suitably used as a dental hardenable composition. [Background technology]
[0002] In dental treatment, dental composite restorative materials, which are used to fill and harden a cavity after caries removal to restore the cavity, are composed mainly of a polymerizable monomer, a filler, and a polymerization initiator. Radical polymerizable monomers are generally used as the polymerizable monomers, but they shrink when hardened, which may impair the adhesion between the tooth and the hardened body in some cases, causing the hardened body to fall off or cause secondary caries. Under such circumstances, dental composite restorative materials with reduced shrinkage during polymerization (polymerization shrinkage) have been studied, and a dental composite restorative material with improved polymerization shrinkage has been proposed that uses a cationic polymerizable monomer such as an epoxy compound or an oxetane compound and a photoacid generator-based photopolymerization initiator (see, for example, Patent Document 1).
[0003] In such cationic polymerization type dental composite restorative materials, because they can be rapidly cured in the oral cavity, it is considered preferable to use, as the photoacid generator-based photopolymerization initiator, an iodonium salt-based photopolymerization initiator or a sulfonium salt-based photopolymerization initiator having high polymerization initiation activity, in particular one having an anion such as trifluoromethanesulfonate or tetrakispentafluorophenylborate, which has low nucleophilicity toward anions (see Patent Document 1).
[0004] However, the above-mentioned cationic polymerization dental composite restorative materials containing highly active photoacid generator-based photopolymerization initiators have a problem of gelling relatively early during storage. Therefore, various additives for suppressing the gelation of photocationically curable compositions have been studied, and a method of adding a phenolic antioxidant in combination with hindered amines that function as hydrogen ion scavengers or salts of organic acids that do not have photoacid generating ability has been proposed (see Patent Documents 2 and 3).
[0005] On the other hand, it is known that when a radiopaque filler is blended into a cationic polymerization type dental composite restorative material for the purpose of imparting radiographic contrast to the cured material, the curing may be inhibited or the storage stability may decrease, and that such problems can be avoided by using a special radiopaque filler prepared by melt processing at high temperatures of 1500 to 3000°C using a plasma melting method or the like (see Patent Document 4). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2007-15946 A [Patent Document 2] JP 2006-249040 A [Patent Document 3] JP 2007-131841 A [Patent Document 4] Special Publication No. 2004-517132 Summary of the Invention [Problem to be solved by the invention]
[0007] As described above, the gelation problem in a cationic polymerizable curable composition containing a highly active photoacid generator-based photopolymerization initiator can be prevented by adding a phenolic antioxidant and a hydrogen ion scavenger in combination. However, in Patent Documents 2 and 3, the curability after long-term storage is not examined, and the effect of long-term storage on the curability is unclear. In addition, since the hydrogen ion scavenger inhibits the progress of cationic polymerization, there is a concern that it will reduce the curing speed when irradiated with light. In particular, in dental applications, since it may be used in the patient's oral cavity, it is required to cure quickly at room temperature. Therefore, if the curability is reduced by adding a hydrogen ion scavenger, there is a risk that the application and method of use will be limited.
[0008] Furthermore, it is unclear whether the above-mentioned additives have an effect of suppressing the occurrence of the above-mentioned phenomena (such as polymerization inhibition and reduced storage stability) that occur when a radiopaque filler is blended. If they cannot be effectively suppressed, a special radiopaque filler as described in Patent Document 4 would have to be used, which would be a major constraint.
[0009] On the other hand, the cationic polymerizable curable composition containing the radiopaque filler described in Patent Document 4 is said to have good storage stability and high reactivity, but its curability after long-term storage is unknown.
[0010] Therefore, an object of the present invention is to provide a cationically polymerizable curable composition which contains a highly active photoacid generator-based photopolymerization initiator and a filler, and which can be stably stored for a long period of time without gelation without using an additive consisting of a combination of a phenolic antioxidant and a hydrogen ion scavenger, and which has good curability not only immediately after preparation (initial curability) but also after long-term storage, and which can be provided with X-ray contrast properties while maintaining such characteristics. [Means for solving the problem]
[0011] The present invention is intended to solve the above problems, and a first aspect of the present invention is a method for producing a polymerizable composition comprising: Iodonium salt-based photoacid generator and / or sulfonium salt-based photoacid generator In a cationically polymerizable curable composition containing an acid generator, The filler has an electronegativity of less than 2.0. Basic Elements that can form oxides B-elements defined as and electronegativity is 2.0-2.8 neutral Elements that can form oxides ( N-elements defined as and the electronegativity exceeds 2.8 acidic Elements that can form oxides B-elements defined as A composite oxide of The acid-base filler comprises a powder of when the abundance ratios of the B-element, the N-element and the A-element in the composite oxide are expressed as a ratio of the mass of the basic oxide:B and the mass of the acidic oxide:A based on the mass of the intermediate oxide:N, the abundance ratios are B / N=0.03 to 3.0 and A / N=1.9 to 3.0, The above The composite oxide powder constituting the acid-base filler is It has basic sites on its surface, pKa 7.2 or more and less than 9.3 This is the region that undergoes a color change when in contact with a Hammett indicator that has a color change pKa within that range. base territory Area and It has acidic sites on its surface. pKa > 3.3 and ≤ 4.8 This is the region that undergoes a color change when in contact with a Hammett indicator that has a color change pKa within that range. acid territory Area and Have death, The content of the acid / base filler is 10 to 400 parts by mass based on 100 parts by mass of the cationic polymerizable monomer. The present invention relates to a cationically polymerizable curable composition.
[0012] In the cationically polymerizable curable composition of the above embodiment (hereinafter also referred to as "cationically polymerizable curable composition of the present invention"), it is preferable that the element capable of forming an oxide having an electronegativity of less than 2.0 is at least one selected from the group consisting of Cs, K, and Na, the element capable of forming an oxide having an electronegativity of 2.0 to 2.8 is at least one selected from the group consisting of Ba, Sr, Ca, Mg, Zn, Li, Al, and Zr, and the element capable of forming an oxide having an electronegativity of more than 2.8 is at least one selected from the group consisting of La, B, Ta, Si, Rh, and P.
[0014] In addition, it is preferable that the filler contains a non-basic filler made of a powder of a substance that does not have a region showing basicity of pKa 7.2 or more, and the content of the non-basic filler is 1 to 380 parts by mass relative to 100 parts by mass of the cationic polymerizable monomer.
[0015] It is also preferable that the average primary particle size of the acid-base filler is 10 to 1000 nm, and the refractive index of the composite oxide constituting the acid-base filler at 25° C. is 1.45 to 1.60 with respect to the sodium d line.
[0016] Furthermore, the cationic polymerizable monomer is an epoxy compound. Yes It is preferable that:
[0017] A second aspect of the present invention is a dental hardenable composition comprising the cationically polymerizable hardenable composition of the present invention (hereinafter also referred to as "dental hardenable composition of the present invention"). Effect of the Invention
[0018] According to the present invention, in a cationic polymerizable curable composition containing an acid generator initiator, gelation can be prevented and storage stability can be improved without using an additive consisting of a combination of a phenolic antioxidant and a hydrogen ion scavenger. Moreover, it is possible to maintain the initial curability even after long-term storage. Furthermore, since the acid / base fillers include those having radiopaque properties, the use of such acid / base fillers makes it possible to obtain a cured product that is radiopaque without separately blending other radiopaque fillers (i.e., radiopaque fillers that may have adverse effects or radiopaque fillers as described in Patent Document 4). shadow It is possible to give the DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Since the cationic polymerizable curable composition of the present invention has the above-mentioned effects, it can be suitably used not only for dental applications but also for various applications requiring such properties, such as dental filling and restorative materials, adhesives, paints, optical materials, etc.
[0020] The reason why such an effect can be obtained is that the composite oxide is composed of an element capable of forming an oxide having an electronegativity of less than 2.0, an element capable of forming an oxide having an electronegativity of 2.0 to 2.8, and an element capable of forming an oxide having an electronegativity of more than 2.8, and has a basicity region of pKa 7.2 or more and less than 9.3, and an acidity region of pKa 3.3 or more and 4.8 or less. powder The detailed mechanism by which this effect is exhibited is not necessarily clear, and the present invention is not bound by any theory, but the inventors presume that it is as follows.
[0021] That is, gelation during storage is thought to be caused by a small amount of acid generated by slight decomposition of the acid generator during storage, and it is thought that the gelation can be prevented by capturing the small amount of acid by the basic sites present in the basic region of the acid-base filler. At this time, since there is an acidic region around the basic region, the acid capturing power of the basic sites is weakened by the influence of the acidic region (acid sites present in the acidic region), and the capturing speed is slowed down, but the basic region and the acidic region of It is believed that even a small amount of acid can be captured because there is an appropriate distance between the two and the time that the acid coexists with the acid is long. In contrast, when a large amount of acid is generated all at once by making the acid generator function (as a polymerization initiator) through light irradiation or the like, the acid cannot be captured and substantially all of the acid can contribute to the polymerization reaction, which is why it is presumed that the initial and long-term curability after storage are well maintained.
[0022] As described above, the cationic polymerizable curable composition of the present invention is most characterized in that it contains a specific amount of an acidic / basic filler, and apart from that, it is not significantly different from conventional cationic polymerizable curable compositions. For example, the cationic polymerizable monomer and acid generator contained in the cationic polymerizable curable composition of the present invention, as well as other fillers (other than the acidic / basic filler) contained as necessary, which are disclosed in Patent Document 1 and are usable in dental cationic curable compositions, can be used without any particular restrictions.
[0023] The cationic polymerizable curable composition of the present invention will be described in detail below, including these. In this specification, unless otherwise specified, the expression "x to y" using numerical values x and y means "x or more and y or less." In such an expression, when a unit is added only to the numerical value y, the unit is also applied to the numerical value x.
[0024] 1.Cationically polymerizable monomers The cationically polymerizable monomer is not particularly limited as long as it is a compound that is polymerized by an acid generated by decomposition of an acid generator, and examples of the monomer that can be used include vinyl ether compounds, epoxy compounds, oxetane compounds, cyclic ether compounds, bicyclic orthoester compounds, cyclic acetal compounds, bicyclic acetal compounds, and cyclic carbonate compounds.
[0025] Specific examples of epoxy compounds that can be suitably used include 1,2-epoxypropane, epichlorohydrin, methyl glycidyl ether, cyclohexene oxide, phenyl glycidyl ether, 1,3-butadiene dioxide, ethylene glycol diglycidyl ether, 1,4-bis(3,4-epoxycyclohexylmethyloxymethyl)benzene, methylbis[2-(7-oxabicyclo[4.1.0]hept-3-yl)ethyl]phenylsilane, glycerol triglycidyl ether, pentaerythritol triglycidyl ether, 3,3',3'',3'''-[(2,4,6,8-tetramethylcyclotetrasiloxane-2,4,6,8-tetrayl)tetra-2,1-ethanediyl]tetrakis[7-oxabicyclo[4.1.0]heptane], and the like.
[0026] Specific examples of oxetane compounds that can be suitably used include trimethylene oxide, 3-methyl-3-oxetanylmethanol, 3,3-diethyloxetane, 3-ethyl-3{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane, 1,4-bis(3-ethyl-3-oxetanylmethyloxy)benzene, 4,4'-bis(3-ethyl-3-oxetanylmethyloxy)biphenyl, ethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, diethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, bis(3-ethyl-3-oxetanylmethyl)diphenoate, and pentaerythritol tetrakis(3-ethyl-3-oxetanylmethyl)ether.
[0027] Specific examples of other cationic polymerizable monomers that can be suitably used include cyclic ether compounds such as tetrahydrofuran and oxepane; bicyclic orthoester compounds such as bicycloorthoesters, spiroorthoesters and spiroorthocarbonates; cyclic acetal compounds such as 1,3,5-trioxane, 1,3-dioxolane, oxepane, 1,3-dioxepane, 4-methyl-1,3-dioxepane and 1,3,6-trioxacyclooctane; bicyclic acetal compounds such as 2,6-dioxabicyclo[2.2.1]heptane, 2,7-dioxabicyclo[2.2.1]heptane and 6,8-dioxabicyclo[3.2.1]octane; and cyclic carbonate compounds such as ethylene carbonate and trimethylene carbonate.
[0028] Among these, epoxy compounds and oxetane compounds are preferably used because of their good polymerizability, etc. The above-mentioned cationically polymerizable monomers may be used alone or in combination of two or more kinds.
[0029] 2. Acid generator As the acid generator, a chemical acid generator, a photoacid generator, a thermal acid generator, etc., which are used as an acid generator capable of polymerizing the above-mentioned cationic polymerizable monomer, can be used without any particular limitation. The amount of the photoacid generator is not particularly limited as long as it is an amount capable of initiating polymerization by light irradiation, but is usually in the range of 0.001 to 10 parts by mass per 100 parts by mass of the cationic polymerizable monomer. From the viewpoint of the polymerization rate and various physical properties (for example, weather resistance and hardness) of the obtained cured body, it is preferable to mix 0.05 to 5 parts by mass based on the above standard.
[0030] In dental applications where the composition is cured in the oral cavity, it is preferable to use a photoacid generator as the acid generator. The photoacid generator means a polymerization initiator made of a compound that is excited by light irradiation, decomposes the photoacid generator, and generates an acid, which becomes a polymerization initiator species and can initiate cationic polymerization. Examples of such photoacid generators include iodonium salt-based photoacid generators, sulfonium salt-based photoacid generators, pyridinium salt-based photoacid generators, and trihalomethyl-S-triazine-based photoacid generators, and any of these can be used. However, since they have high polymerization activity, it is preferable to use an iodonium salt-based photoacid generator and / or a sulfonium salt-based photoacid generator, and it is particularly preferable to use an iodonium salt-based photoacid generator. In addition, for photoacid generators that do not absorb light in the near ultraviolet to visible range, it is preferable to mix about 0.001 to 20 moles, preferably 0.005 to 10 moles of a sensitizer compound with 1 mole of the photoacid generator in order to make the photoacid generator exhibit polymerization activity by irradiation with such light.
[0031] Examples of iodonium salt-based photoacid generators that can be suitably used include diaryliodonium salt-based compounds consisting of cations such as diphenyliodonium, bis(p-chlorophenyl)iodonium, ditolyliodonium, bis(p-tert-butylphenyl)iodonium, p-isopropylphenyl-p-methylphenyliodonium, bis(m-nitrophenyl)iodonium, p-tert-butylphenylphenyliodonium, p-methoxyphenylphenyliodonium, bis(p-methoxyphenyl)iodonium, p-octyloxyphenylphenyliodonium, p-phenoxyphenylphenyliodonium, and bis(p-dodecylphenyl)iodonium, and anions such as chloride, bromide, p-toluenesulfonate, trifluoromethanesulfonate, tetrafluoroborate, tetrakispentafluorophenylborate, tetrakispentafluorophenylgallate, hexafluorophosphate, hexafluoroarsenate, and hexafluoroantimonate. Among these, from the viewpoints of solubility in cationic polymerizable monomers and polymerization activity, it is preferable to use a compound having hexafluoroantimonate, tetrakispentafluorophenylborate or tetrakispentafluorophenylgallate as the anion, and from the viewpoint of low toxicity, it is particularly preferable to use a compound having tetrakispentafluorophenylborate as the anion.
[0032] In addition, examples of sulfonium salt compounds that can be suitably used as a component of a sulfonium salt-based photoacid generator include chlorides, bromides, p-toluenesulfonates, trifluoromethanesulfonates, tetrafluoroborate, tetrakispentafluorophenylborate, tetrakispentafluorophenylgallate, hexafluorophosphate, hexafluoroarsenate, and hexafluoroantimonate salts of triphenylsulfonium, p-tolyldiphenylsulfonium, p-tert-butylphenyldiphenylsulfonium, diphenyl-4-phenylthiophenylsulfonium, and the like.
[0033] In addition, examples of sensitizers used in combination with the photoacid generator include acridine dyes, benzoflavin dyes, condensed polycyclic aromatic compounds such as anthracene and perylene, phenothiazine, diaryl ketone compounds, α-diketone compounds, and coumarin compounds that absorb light in the near ultraviolet to visible range.
[0034] 3.Filling material The filler to be blended in the cationic polymerizable curable composition of the present invention must contain at least 20 to 400 parts by mass, preferably 40 to 150 parts by mass, of the acidic / basic filler relative to 100 parts by mass of the cationic polymerizable monomer. If this condition is not satisfied, the above-mentioned effect cannot be obtained. In order to ensure the proper properties (operability) as a dental curable composition, the filler may contain 1 to 380 parts by mass, particularly 60 to 190 parts by mass, of a non-basic filler made of a powder of a substance that does not have a basicity region of pKa 7.2 or more relative to 100 parts by mass of the cationic polymerizable monomer. When a non-basic filler is blended, the stabilizing effect tends to decrease, but if the blending amount is at this level, a stabilizing effect that can withstand practical use can be obtained. Below, fillers such as acidic / basic fillers and non-basic fillers will be described in detail.
[0035] 3-1. Acid / base fillers In the present invention, the acid-base filler refers to a composite oxide of an element capable of forming an oxide having an electronegativity of less than 2.0 (hereinafter also referred to as "acidic oxide"), an element capable of forming an oxide having an electronegativity of 2.0 to 2.8 (hereinafter also referred to as "intermediate oxide"), and an element capable of forming an oxide having an electronegativity of more than 2.8 (hereinafter also referred to as "acidic oxide"), the composite oxide having a basic region of pKa 7.2 or more and less than 9.3 (hereinafter also referred to as "basic region") and an acidic region of pKa exceeding 3.3 and not more than 4.8 (hereinafter also referred to as "acidic region"). powder "filler" means a filler material consisting of a solid.
[0036] Here, the electronegativity of an oxide means a weighted average of the Pauling electronegativities of the elements constituting the oxide, based on the ratio of each element contained. For example, the electronegativity of boron oxide (BO) is calculated based on the electronegativity of boron: 2.04, the electronegativity of oxygen: 3.44, the number of boron atoms: 2, the number of oxygen atoms: 3, and the total number of atoms: 5, as follows: Formula: {(2.04×2)+(3.44×3)} / 5=2.88 Therefore, the electronegativity is 2.88. The electronegativity values determined in this way for representative oxides are shown in Table 1.
[0037] [Table 1]
[0038] In addition, the basic region, which is a region showing a basicity of pKa 7.2 or more and less than 9.3, means a region that has a basic site on the surface and changes color when contacted with a Hammett indicator having a color change pKa within the above pKa range. The presence of the basic region can be confirmed by a color change when contacted with a Hammett indicator. That is, Table 2 shows representative Hammett indicators and their color change pKas, and the indicator can be confirmed by the fact that the indicator changes color when contacted with bromothymol blue, which has a color change pKa of 7.2, and various Hammett indicators, which have a color change pKa of 7.2 or more and less than 9.3, and does not change color when contacted with phenolphthalein, which has a color change pKa of 9.3. Similarly, the acidic region, which is a region showing an acidity of pKa 3.3 or more and less than 4.8, means a region that has an acidic site on the surface and changes color when contacted with a Hammett indicator having a color change pKa within the above pKa range. Its presence can be confirmed by the fact that it changes color when it comes into contact with a Hammett indicator such as methyl red or 4-phenylazo-1-naphthylamine, which has a color change pKa of more than 3.3 and not more than 4.8, but does not change color when it comes into contact with a Hammett indicator whose color change pKa is outside the above range, such as methyl yellow (color change pKa: 3.3) or 2-aminoazotoluene (color change pKa: 2.0), which has a color change pKa of 3.3 or less. In the present invention, the amount of the composite oxide is determined by the following: powder Several samples were prepared by suspending 1 g of the substance, and 0.3 ml of a 1% by mass toluene solution of a Hammett indicator with each color change pKa was dropped into each sample, after which the suspension was shaken and the presence or absence of a color change in the suspension was visually confirmed to confirm the presence or absence of an acidic / basic region.
[0039] [Table 2]
[0040] In the composite oxide constituting the acid-base filler, an element capable of forming an oxide (basic oxide) having an electronegativity of less than 2.0 is defined as a B-element, an element capable of forming an oxide (intermediate oxide) having an electronegativity of 2.0 to 2.8 is defined as a N-element, and an element capable of forming an oxide (acidic oxide) having an electronegativity of more than 2.8 is defined as an A-element. The B-element is preferably at least one selected from the group consisting of Cs, K, and Na. The N-element is preferably at least one selected from the group consisting of Ba, Sr, Ca, Mg, Zn, Li, Al, and Zr. The A-element is preferably at least one selected from the group consisting of La, B, Ta, Si, Rh, and P.
[0041] Furthermore, from the viewpoint of effectiveness, the abundance ratios of the B-element, the N-element and the A-element in the composite oxide constituting the acid-base filler are preferably B / N=0.03 to 3.0 and A / N=1.9 to 3.0, and more preferably B / N=2.0 to 3.0 and A / N=2.0 to 3.0, expressed as the ratio of the mass of the basic oxide:B and the mass of the acidic oxide:A based on the mass of the intermediate oxide:N.
[0042] For acidic and basic fillers, surface treatment can be performed to improve affinity with various monomers, but it is necessary to note that the surface treatment may change the surface properties of the filler, i.e., basicity or acidity. In view of reactivity with the surface treatment agent when performing surface treatment, it is preferable that the A-element contains Si.
[0043] The composite oxide constituting the acid-base filler powder The body is made of said basic oxide. powder The intermediate oxide powder and the acidic oxide. powder The mixture is mixed to satisfy the above B / N and A / N. powder It can be obtained by melting or sintering the raw material at high temperature and then crushing it appropriately. It is also made of a composite oxide of available B-elements, N-elements, and A-elements. powderIf the content ratio of these materials satisfies the above conditions and no special surface treatment is performed, it is generally considered that the material can be used as an acid-base filler. If the material is surface-treated, it can be confirmed whether it is an acid-base filler or not by the confirmation method using a Hammett indicator described above.
[0044] In addition, when used in a dental hardenable composition, the refractive index of the composite oxide at 25°C for sodium d-line is preferably 1.45 to 1.60, because light scattering between the polymerizable monomer and the polymer is unlikely to occur and the composite oxide is excellent in aesthetics when filled into a tooth structure. In addition, the refractive index of the composite oxide at 25°C for sodium d-line is preferably 1.45 to 1.60, because the composite oxide is easy to obtain a gloss when polished after filling into a tooth structure and is excellent in workability and aesthetics. powder The average primary particle size of the particles is preferably from 10 to 1000 nm, and more preferably from 100 to 600 nm.
[0045] Furthermore, in order to impart X-ray contrast without blending other X-ray-opaque fillers, it is preferable that the acid-base filler has X-ray opacity. In order to impart X-ray opacity, it is sufficient to include an element having an atomic number of at least 30 as a B-element, N-element, or A-element.
[0046] 3-2.Non-basic fillers In the present invention, a non-basic filler is a substance that does not have a region showing a basicity of pKa 7.2 or more. powder The term "neutral filler" refers to a filler made of a substance. As the non-basic filler, an oxide of the N-element or a composite oxide of a plurality of different N-elements can be used. These neutral fillers may be blended as they are, or may be blended as a so-called "organic-inorganic composite filler" in which the filler is mixed with a radical polymerizable monomer, cured, and then pulverized to form a composite with a resin. When blending as it is, it is preferable to perform a surface treatment using a silane coupling agent or the like.
[0047] Furthermore, the basic oxide or the composite oxide constituting the acid-base filler may be surface-treated to have no region exhibiting a basicity of pKa 7.2 or more.
[0048] In the non-basic filler, the oxide or composite oxide constituting the filler preferably has a refractive index of 1.45 to 1.60 at 25° C. with respect to the sodium d line. powder The average primary particle size of the particles is preferably 10 to 1000 nm, and more preferably 100 to 600 nm.
[0049] Furthermore, the non-basic filler may be an organic filler. Suitable organic fillers include those made of organic polymers such as polymethyl methacrylate, polyethyl methacrylate, methyl methacrylate-ethyl methacrylate copolymer, crosslinked polymethyl methacrylate, crosslinked polyethyl methacrylate, ethylene-vinyl acetate copolymer, styrene-butadiene copolymer, acrylonitrile-styrene copolymer, and acrylonitrile-butadiene-styrene copolymer. powder You can raise your body.
[0050] 4.Other Ingredients 4-1.Radical polymerizable monomers The cationic polymerizable curable composition of the present invention may contain an addition polymerization type radical polymerizable monomer such as a (meth)acrylate monomer, if necessary. By containing a radical polymerizable monomer, the apparent curing time can be shortened. However, since the addition polymerization type radical polymerizable monomer may cause phase separation from the cationic polymerizable monomer after curing, it is not preferable to contain a large amount of the addition polymerization type radical polymerizable monomer.
[0051] When the radical polymerizable monomer is blended, the blending amount thereof is preferably 43 parts by mass or less, and more preferably 12 parts by mass or less, per 100 parts by mass of the cationic polymerizable monomer.
[0052] Specific examples of such radical polymerizable monomers include methyl (meth)acrylate, glycidyl (meth)acrylate, 2-cyanomethyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, allyl (meth)acrylate, 2-hydroxyethyl mono(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, nonaethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol Examples of the (meth)acrylate monomers include ricol di(meth)acrylate, 2,2-bis[4-(meth)acryloyloxyethoxyphenyl]propane, 2,2-bis[4-(meth)acryloyloxyethoxyethoxyphenyl]propane, 2,2-bis{4-[3-(meth)acryloyloxy-2-hydroxypropoxy]phenyl}propane, 1,4-butanediol di(meth)acrylate, 1,3-hexanediol di(meth)acrylate, urethane di(meth)acrylate, and trimethylolpropane di(meth)acrylate.
[0053] When these radical polymerizable monomers are blended, it is preferable to blend a radical polymerizable initiator together. The radical polymerizable initiator is not particularly limited as long as it does not adversely affect the storage stability of the cationic polymerizable curable composition of the present invention, but when a photoacid generator is used, it is preferable to use a photopolymerization initiator.
[0054] 4-2.Various additives, etc. The cationically polymerizable curable composition of the present invention may contain various additives, such as a polymerization inhibitor, an ultraviolet absorber, a dye, an antistatic agent, a pigment, a fragrance, an organic solvent, and a thickener, as necessary, within a range that does not impair the effects of the present invention.
[0055] 5. Method for producing and using the cationically polymerizable curable composition of the present invention The cationic polymerizable curable composition of the present invention can be produced by mixing each component. Specifically, the components are weighed out in a predetermined amount and mixed to form a paste. At this time, the mixing conditions are adopted under conditions under which no acid is generated depending on the type of acid generator used. For example, when a photoacid generator is used, it is necessary to mix in a dark place, and when a thermal acid generator is used, it is necessary to mix at room temperature or at a low temperature. Then, the produced cationic polymerizable monomer of the present invention is stored in the dark or at room temperature or at a low temperature until use. When a chemical acid generator is used, the constituent components are divided and mixed with other components so that the chemical acid generator does not function, and multiple agents containing each component are prepared, stored in a divided state, and each agent is mixed when used.
[0056] As a means for curing the cationic polymerizable curable composition of the present invention, a known polymerization means may be appropriately adopted according to the polymerization initiation mechanism of the polymerization initiator used, and specifically, light irradiation by a light source such as a carbon arc, a xenon lamp, a metal halide lamp, a tungsten lamp, a fluorescent lamp, sunlight, a helium cadmium laser, an argon laser, or heating using a heating polymerization device, or a combination of these, etc., may be used without any restrictions. When polymerizing by light irradiation, the irradiation time varies depending on the wavelength and intensity of the light source, the shape and material of the cured body, so it may be determined in advance by preliminary experiments, but it is generally preferable to adjust the blending ratio of various components so that the irradiation time is in the range of about 5 to 60 seconds. EXAMPLES
[0057] The present invention will be specifically illustrated below with reference to examples, but the present invention is not limited to these examples in any way.
[0058] First, in the Examples and Comparative Examples, the substances used as raw materials for the cationically polymerizable curable compositions prepared, their abbreviations, and the evaluation methods for the prepared cationically polymerizable curable compositions will be described.
[0059] 1. Substances and their abbreviations 1-1.Cationically polymerizable monomers EP-1: A compound represented by the following formula (KR470, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0060] [ka]
[0061] OX-1: A compound represented by the following formula (manufactured by Toagosei Co., Ltd., OXT-121)
[0062] [ka]
[0063] 1-2. Polymerization initiator (1) Photoacid generator DPIB: 4-isopropyl-4'-methyldiphenyliodonium tetrakis(pentafluorophenyl)borate (Tokyo Chemical Industry Co., Ltd.) (2) Sensitizer CQ: Camphorquinone (Tokyo Chemical Industry Co., Ltd.).
[0064] 1-3. Filling material (1) Acid-base fillers The acidic / basic fillers used were F1, F2 and F3 (all manufactured by SCHOTT AG), which are made of composite oxides having the compositions shown in Table 3. The composition of each oxide-based filler shown in Table 3 is based on the results of fluorescent X-ray measurement, and is expressed as the content of each element (B-element, N-element and A-element) expressed on the mass basis of the oxide of each element. The pH of the basic region and the pH of the acidic region shown in Table 3 were determined by dissolving the fillers in 3 ml of toluene that had been dehydrated using a molecular sieve, as described above. powderA number of samples were prepared by suspending 1 g of the substance, and 0.3 ml of a 1% by mass toluene solution of a Hammett indicator with each color change pKa was dropped into each sample, after which the suspension was shaken and the presence or absence of a color change in the suspension was visually confirmed to confirm the presence or absence of acidic and basic sites. Furthermore, the average primary particle diameter of each filler and the refractive index for sodium d line at 25°C are as follows. F1: Average primary particle diameter 4000nm, refractive index 1.58 F2: Average primary particle size 400 nm, refractive index 1.52 F3: Average primary particle size 400 nm, refractive index 1.52.
[0065] (2) Fillers other than acid-base fillers (other fillers) (2-1) Other oxide-based fillers As oxide-based "other fillers", RF1 to RF6 (all manufactured by SCHOTT AG) and RF7 (prepared by the sol-gel method) made of composite oxides having the compositions shown in Table 3, as well as SiO2: silica (prepared by the fusion method with an average primary particle diameter of 1000 nm and a refractive index of 1.46) and Al2O3: alumina (manufactured by Tokyo Chemical Industry Co., Ltd.) were used. RF2-ST is RF2 surface-treated with methacrylate-3-(trimethoxysilyl)propyl-3-(methacryloyloxy)propyltrimethoxysilane, which is a silane coupling agent. The content of F in RF5 is not based on the oxide but on the mass of the element.
[0066] The average primary particle diameters of RF1 to RF7 and their refractive indices for the sodium d line at 25°C are shown below. RF1: Average primary particle size 1500nm, refractive index 1.53 RF2: Average primary particle size 260 nm, refractive index 1.52 RF3: Average primary particle size 700 nm, refractive index 1.52 RF4: Average primary particle size 700 nm, refractive index 1.53 RF5: Average primary particle size 700 nm, refractive index 1.53 RF6: Average primary particle size 1000nm, refractive index 1.55 RF7: average primary particle size 260 nm, refractive index 1.52.
[0067] (2-2) Inorganic and organic salt-based fillers As inorganic salt-based and organic salt-based "other fillers", the following were used: NaF: sodium fluoride (manufactured by Tokyo Chemical Industry Co., Ltd.), Na2CO3: sodium carbonate (manufactured by Tokyo Chemical Industry Co., Ltd.), Na2SO4: sodium sulfate (manufactured by Tokyo Chemical Industry Co., Ltd.), and DBS-Na: sodium dodecylbenzenesulfonate (manufactured by Tokyo Chemical Industry Co., Ltd.) shown in Table 3.
[0068] [Table 3]
[0069] 2. Evaluation method of cationic polymerizable curable composition 2-1. Curability evaluation The cationic polymerizable curable compositions prepared in each of the Examples and Comparative Examples were filled into a polypropylene mold with an inner diameter of 0.7 cm and a depth of 0.1 cm. Then, using a dental light irradiator (TOKUSO POWER LITE, manufactured by Tokuyama Corporation), light was irradiated for 20 seconds at an irradiation distance of 0.5 cm. The compositions that were fully cured after irradiation were marked with an ◯, and those that had uncured parts or were not cured at all were marked with an ×.
[0070] 2-2 Storage stability evaluation (1) Storage period until gelation The compositions prepared in each Example and Comparative Example were stored in a thermostatic chamber at 50°C under light-shielded conditions. The curable compositions were taken out of the thermostatic chamber every other day and allowed to cool to room temperature in a dark place, after which the properties of the curable compositions were inspected with a plastic spatula. In this case, the number of days when the composition lost a large amount of fluidity and the viscosity increased when touched with the spatula, or became jelly-like without flowing, was recorded as the number of days of storage until gelation (number of days to gelation), compared with the composition immediately after preparation.
[0071] (2) Hardening after storage The curability of the composition stored in the same manner as in (1) was inspected by the method shown in 2-1. The number of days when the composition showed an X was recorded as the number of days of storage until the curability decreased (number of days for which the curability decreased).
[0072] (3) Storage period The storage period was determined as the shorter of (1) or (2).
[0073] Example 1 To 100 parts by mass of cationic polymerizable monomer consisting of 70 parts by mass of EP-1 and 30 parts by mass of OX-1, 1.5 parts by mass of DPIB and 0.3 parts by mass of CQ were added as a polymerization initiator, and the mixture was stirred for 6 hours to prepare a liquid composition. To this liquid composition, 150 parts by mass of F1 was added as a filler to 100 parts by mass of cationic polymerizable monomer, and mixed in an agate mortar, and the mixture was evacuated and degassed to remove air bubbles, to obtain a paste-like cationic polymerizable curable composition.
[0074] The curability and storage stability of the resulting cationically polymerizable curable composition were evaluated, and the results are shown in Table 4.
[0075] Examples 2 to 6, Comparative Examples 1 to 17 A cationically polymerizable curable composition was prepared in the same manner as in Example 1, except that the filler to be blended in was changed as shown in Table 4, and the curability and storage stability of the composition were evaluated. The results are also shown in Table 4.
[0076] [Table 4]
[0077] As shown in Table 4, in Comparative Example 1, which did not contain any acidic or basic filler or other filler, the initial curing property was good, and the number of days to gel was 39 days. On the other hand, in Examples 1 to 6, which contained an acidic or basic filler, the initial curing property was excellent, and further, the number of days to gel was 140 days or more, which was significantly longer than that of Comparative Example 1, and the number of days until the curing property decreased was also extremely long, at 172 days or more. In contrast, in Comparative Examples 2 to 5, in which RF1 and RF2, which are the same BNA-based composite oxides but do not fall under the category of acidic / basic fillers, were added, the gelation period was shorter than in Comparative Example 1. Similarly, in Comparative Examples 6 to 12, in which "other fillers" based on composite oxides other than BNA-based composite oxides and silica were added, the gelation period was shorter than in Comparative Example 1. In Comparative Example 13, in which alumina was added, the gelation period was longer than in Comparative Example 1, but the extent of this was inferior to that of the Examples, and the number of days until the hardening property decreased (42 days) was also significantly shorter than that of the Examples. Furthermore, in Comparative Examples 14 to 17, in which "other fillers" based on inorganic salts and organic salts were added, the gelation period was longer, but the number of days until the hardening property decreased was 30 days to 2 days, which is significantly shorter (inferior) than that of the Examples, presumably because these fillers are basic.
[0078] Examples 7 to 12, Comparative Examples 18 to 20 Compositions were prepared in the same manner as in Example 1, except that the type and amount of filler used in Example 1 were changed as shown in Table 5, and their curability and storage stability were evaluated. The results are also shown in Table 5.
[0079] [Table 5]
[0080] As shown in Table 5, the cationic polymerizable curable compositions of Examples 7 to 12, which are formulated by combining an acidic / basic filler with a non-basic filler, also have improved storage life compared to Comparative Example 1, which does not contain an acidic / basic filler or other fillers. Also, the storage life is significantly longer than that of Comparative Examples 18 to 20, which do not contain an acidic / basic filler and contain a non-basic filler at the same filling rate as in each Example.
Claims
1. A cationically polymerizable curable composition comprising a cationically polymerizable monomer, a filler, and an iodonium salt-based photoacid generator and / or a sulfonium salt-based photoacid generator, The filler includes an acid-base filler made of a powder of a composite oxide of a B-element, which is defined as an element capable of forming a basic oxide having an electronegativity of less than 2.0, an N-element, which is defined as an element capable of forming a neutral oxide having an electronegativity of 2.0 to 2.8, and an B-element, which is defined as an element capable of forming an acidic oxide having an electronegativity of more than 2.8; when the abundance ratios of the B-element, the N-element and the A-element in the composite oxide are expressed as the ratio of the mass of the basic oxide:B and the mass of the acidic oxide:A based on the mass of the intermediate oxide:N, the abundance ratios are B / N=0.03 to 3.0 and A / N=1.9 to 3.0, The composite oxide powder constituting the acid-base filler is a basic region that has a basic site on its surface and undergoes a color change when contacted with a Hammett indicator having a color change pKa in the range of 7.2 to less than 9.3; an acidic region, which has acidic sites on its surface and undergoes a color change when contacted with a Hammett indicator having a color change pKa in the range of more than pKa 3.3 to 4.8; having The content of the acidic / basic filler is 10 to 400 parts by mass based on 100 parts by mass of the cationic polymerizable monomer. A cationically polymerizable curable composition comprising:
2. The cationically polymerizable curable composition according to claim 1, wherein the element capable of forming an oxide having an electronegativity of less than 2.0 is at least one selected from the group consisting of Cs, K, and Na, the element capable of forming an oxide having an electronegativity of 2.0 to 2.8 is at least one selected from the group consisting of Ba, Sr, Ca, Mg, Zn, Li, Al, and Zr, and the element capable of forming an oxide having an electronegativity of more than 2.8 is at least one selected from the group consisting of La, B, Ta, Si, Rh, and P.
3. the filler includes a non-basic filler made of a powder of a substance that does not have a region exhibiting a basicity of pKa 7.2 or more, and the content of the non-basic filler is 1 to 380 parts by mass relative to 100 parts by mass of the cationic polymerizable monomer; The cationically polymerizable curable composition according to claim 1 or 2.
4. The cationically polymerizable curable composition according to any one of claims 1 to 3, wherein the average primary particle size of the acidic / basic filler is 10 to 1000 nm, and the refractive index of the complex oxide constituting the acidic / basic filler at 25°C is 1.45 to 1.60 with respect to sodium d line.
5. The cationically polymerizable curable composition according to any one of claims 1 to 4, wherein the cationically polymerizable monomer is an epoxy compound.
6. A dental hardenable composition comprising the cationically polymerizable hardenable composition according to any one of claims 1 to 5.
Citation Information
Patent Citations
Cation-curable dental material
JP2004517132A
Dental curable composition
JP2006249040A
Cationically curable composition for dental use
JP2007015946A
Photocationically curable composition
JP2007131841A
Glass filler material and manufacturing method thereof
JP2007515450A